Fake Gold: Gold Purity Measurement Using Non Destructive Method - Mohd Nor, Fazrul; Rahman Tamuri, Abd; Khamim Ismail, Abd (International Journal of Engineering and Technology, 2019)
Determination of the gold bar purity by non-destructive method remains one of the most challenging in gold industry especially when the tungsten is inside the gold bar. The existing instruments have a limitation to determine the fineness of gold bar and it was difficult to detect the tungsten inside the gold bar due to the density of tungsten is almost similar to the density of gold. This report presents the limitation of the non-destructive method instruments such as densimeter, weighing balance, x-ray fluorescence (XRF) and ultrasonic. Furthermore, the research on the non-destructive method by other researchers also will be discussed in this report.Â Â